2002
DOI: 10.1103/physrevb.65.155317
|View full text |Cite
|
Sign up to set email alerts
|

Kondo effect and bistability in a double quantum dot

Abstract: We study theoretically the out-of-equilibrium transport properties of a double quantum dot system in the Kondo regime. We model the system by means of a two-impurity Anderson Hamiltonian. The transport properties are characterized by Kondo effect properties, however, superimposed them, the system possesses novel non-linear bistability behavior.Recently experiments on quantum dots (QDs) at temperatures (T ) below the Kondo temperature (T k ) have shown that new physics emerges when their transport properties ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…7 Double QDs systems behavior is recently under careful investigation because of the variable inter-dot tunneling coupling, 8 which is the physical reason for non-linearity formation and consequently for existence of such phenomena as bifurcations, 910 and bi-stability, 11 . 12 Electron transport in QDs is strongly governed by Coulomb interaction between localized electrons, the ratios between tunneling transfer amplitudes, QDs coupling and of course by the initial conditions, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Double QDs systems behavior is recently under careful investigation because of the variable inter-dot tunneling coupling, 8 which is the physical reason for non-linearity formation and consequently for existence of such phenomena as bifurcations, 910 and bi-stability, 11 . 12 Electron transport in QDs is strongly governed by Coulomb interaction between localized electrons, the ratios between tunneling transfer amplitudes, QDs coupling and of course by the initial conditions, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Parameter of p indicates the distance between two-rings. The system assumed in equilibrium, is modeled by using a non interacting Anderson tunneling Hamiltonian [5][6] which can be written as: In this section, simulated results including the electronic conductance through quantum wire with side-coupled asymmetric QD-rings as a scatter system are presented and discussed. Figure2 shows, the dimensionless conductance (g = G/(2e2/h) = T) is plotted versus Fermi energy in units of μ ( ε / μ).…”
Section: Introductionmentioning
confidence: 99%
“…This is because coupling to the continuum states shows an even-odd parity effect in the conductance when the Fermi energy is localized at the center of the energy band [3][4][5][6][7][8][9]. The systems such as uniform QD array [10], nano-wires [11] and nano-ring [12] which are side-coupled to a QW act as a scatter system for electron transmission through the QW and have a major effect on electronic conductance of nano-device. For a uniform QD-chains array with M sites, it was shown that the transmission characteristic has M anti-resonances and M-1 resonance, M mini-gaps and M-1 allowed mini-bands arise [10].…”
Section: Introductionmentioning
confidence: 99%